Pelatihan Asertivitas untuk Memperkuat Self Confidence pada Mahasiswa di Yogyakarta - Wenty Lestari; Kamsih Astuti; Novia Sinta Rochwidowati (Jurnal Psikologi, 2020)
The study aims to examine the influence of assertiveness training toward increasing self confidence in college students woman dormitories "DD" West Kalimantan in Yogyakarta. The subjects of the study were 10 college students woman who had low self confidence and assertiveness, divided into two groups namely experiment and control of each of the five subjects. The research design used was pretest-posttest control group design, with U-Mann Whitney analysis and Wilcoxon Rank Test analysis. U-Mann Whitney analysis results showed a significant difference in the self confidence and assertiveness score of the experimental group and the control group that is self confidence (p=0.009 <0.05) and assertiveness (p=0.009 <0.05). Average subjects result of self confidence in the experimental group (84.40) and the control group (74.20), and the average value of assertiveness subjects in the experimental group (102.20) and the control group (89.20). The result of the Wilcoxon Rank Test showed a significant difference in the self confidence and assertiveness score of the  experimental group between before and after being given assertiveness training, that is confidence (p=0,043 < 0,05) and assertiveness (p=0,043 < 0,05). This result are supported on self confidence score before training (75.20) increasing to (84.40) after assertiveness training and the assertiveness score before training (92.40) increased to (102.20) after assertiveness training. Based on the explanation above, it can be concluded that assertiveness training can improve self confidence in college students woman dormitories "DD" West Kalimantan in Yogyakarta.